INVESTASI ASING DAN ALIH TEKNOLOGI DALAM PRESPEKTIF HUKUM EKONOMI - Jamaluddin, Fitriani (IAIN Palopo, 2017)
The aim of this research, (1) To explain about the relation between investment and economic law (2) To know about the relation between foreign investment and the growth of Indonesia Economic. (3) To know about the shape of redirects of foreign investment in Indonesia. This research is normatif research. And the type of this research is library research. The result of this research, noticing that investment is closely related to economic law,investment consideration in a country decided by the regulation of economic law. The result of this research also noticing that there are not spesific regulation about technology transfer, In Undang-Undang nomor 25 Tahun 2007 About direct investment, there are not single article talking about technology transfer. Technology transfer in this case not only about machine but also about knowledge that can help to build Knowledge in Indonesia.